Masters of Manufacturing Herbert B. Voelcker. (Manufacturing Engineering)
This is the eighth annual installment in an article series we call Masters of Manufacturing. In these articles, we honor a distinguished figure in manufacturing technology and by doing so, we hopeto remind readers that a career of great achievement in manufacturing is still possible.